2010
DOI: 10.1152/japplphysiol.01213.2009
|View full text |Cite
|
Sign up to set email alerts
|

Motor unit behavior during submaximal contractions following six weeks of either endurance or strength training

Abstract: The study investigated changes in motor output and motor unit behavior following 6 wk of either strength or endurance training programs commonly used in conditioning and rehabilitation. Twenty-seven sedentary healthy men (age, 26.1 ± 3.9 yr; mean ± SD) were randomly assigned to strength training (ST; n = 9), endurance training (ET; n = 10), or a control group (CT; n = 8). Maximum voluntary contraction (MVC), time to task failure (isometric contraction at 30% MVC), and rate of force development (RFD) of the qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
134
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(149 citation statements)
references
References 57 publications
14
134
1
Order By: Relevance
“…Large volumes of endurance training may inhibit adaptations to strength training (15) and thus potentially quest for a larger frequency of strength maintenance training. Indeed, endurance training has been shown to lower the maximum shortening velocity of type II fibers, reduce motor unit discharge rates, and to slightly reduce peak tension development in all fiber types (9,10,30,(33)(34). In accordance with the latter findings, endurance training has been associated with reduced vertical jumping ability (5), strength (5,19), and unchanged or slightly reduced CSA of muscle fibers (9,15,(33)(34).…”
Section: Discussionmentioning
confidence: 52%
“…Large volumes of endurance training may inhibit adaptations to strength training (15) and thus potentially quest for a larger frequency of strength maintenance training. Indeed, endurance training has been shown to lower the maximum shortening velocity of type II fibers, reduce motor unit discharge rates, and to slightly reduce peak tension development in all fiber types (9,10,30,(33)(34). In accordance with the latter findings, endurance training has been associated with reduced vertical jumping ability (5), strength (5,19), and unchanged or slightly reduced CSA of muscle fibers (9,15,(33)(34).…”
Section: Discussionmentioning
confidence: 52%
“…Maximal H to M (H/M) wave ratios of the triceps surae muscles are higher in endurance-trained compared to power-trained and sedentary individuals (Rochcongar et al 1979;Maffiuletti et al 2001), suggesting that endurance training may increase excitability of the spinal cord. Further, motor unit firing rates during a brief non-fatiguing contraction at 30 % maximal voluntary contraction (MVC) were lower after 6 weeks of aerobic cycle ergometer training (Vila-Cha et al 2010). In contrast, the same study also found that motor unit firing rates during brief non-fatiguing contractions were higher after resistance training (Vila-Cha et al 2010).…”
Section: Introductionmentioning
confidence: 93%
“…Previous studies have also shown that time to task failure of sustained contraction was prolonged following resistance training, most likely due to neural adaptations at level of central nerve system 8 . Cross-training is the process whereby training of one limb gives rise to enhancements in the performance of the opposite, untrained limb 9 .…”
Section: Introductionmentioning
confidence: 96%